Impact of non-gated computed tomography on the timing of invasive strategy of patients with non-ST-elevation acute coronary syndrome - Miyagawa, Masatsugu; Arai, Riku; Takahashi, Kurara; Nakajima, Yuki; Migita, Shohei; Mizobuchi, Saki; Tanaka, Yudai; Fukumoto, Katsunori; Morikawa, Tomoyuki; Mineki, Takashi; Kojima, Keisuke; Murata, Nobuhiro; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: This study aimed to examine the clinical role of non-gated computed tomography (CT) to rule out fatal chest pain in patients with non-ST-elevation acute coronary syndrome (NSTE-ACS), focusing on the time of arrival at hospital to coronary angiography (CAG) and peak CK.We retrospectively examined 196 NSTE-ACS patients who had admitted urgently diagnosed NSTE-ACS and underwent percutaneous coronary intervention between March 2019 and October 2022. Based on whether patients underwent a CT scan and the presence or absence of perfusion defects on the CT image, those were divided into three groups (Not CT group, CT and defectgroup, or CT and defect+ group). Results: After the initial admission for NSTE-ACS, 40 patients (20.4%) underwent non-gated CT prior to CAG. Among these 40 patients, 27 had a perfusion defect on the CT scan. The incidence of contrast-induced nephropathy was not different among the three groups. The CT and defect+ group had a shorter arrival-to-CAG time than the Not CT group. In NSTE-ACS patients with elevated CK levels, the CT and defect+ group had lower peak CK levels than the Not CT group. Conclusion: NSTE-ACS patients with perfusion defect on non-gated CT had a shorter time from arrival to CAG, which might be associated with a lower peak CK. Non-gated CT might be useful for early diagnosis and early revascularization in the clinical setting of NSTE-ACS.